PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 2 RANAH BATAHAN - Sari, Hardina; Rismen, Sefna; Pratiwi, Merina (Pendidikan Matematika, 2013)
The introduction of this research Â by the lack of studentâs mathematical problem solving. It can be supported by the result of examination of students SMPN 2 Ranah Batahan academic year 2012/2013, based on the percentage of studentâs succeed in the first semester. Furthermore thisÂ  research hasÂ  purpose to find out mathematical in problem solving at eightth the grade of SMPN 2 Ranah Batahan by using cooperative learning strategy type Snowball Throwing is better than use conventional strategy.The design of this research is experiment. It seems that there are experiment and control class. Sample at this research took the population as all of eightth grade SMPN 2 Ranah Batahan students and the sample was VIII4 as experiment and VIII3 as control class. The instrument use here was a essay form and the reliabilitytest was 0,63. The result of hypothesis testing with one side oft test, at hypothesis the ttest greater than ttable,it can be concluded that students mathematical in problem solving use Snowball Throwing us better than conventional strategy at class student of eightth grade of SMPN 2 Ranah Batahan.